Solving Elasto-Static Bounded Problems with a Novel Arbitrary-Shaped Element - Hamidreza Khalaj-Hedayati; Mohammad Iman Khodakarami (Civil Engineering Journal, 2019)
A simple method to analysis any arbitrary domain shapes with a single element which based on Decoupled Scaled Boundary Finite Element Method is presented in this paper. The introduced element is based on boundary finite element method which helps to modelling curve and sharp boundaries with acceptable accuracy. Shape functions and mapping functions are similar to Decoupled Scaled Boundary Finite Element Method but locating center origin (LCO) is relocated in this method from corners with direct view to whole domain into shape center and formulation and behavior of the method is developed for the element. The most important advantageous of this technique is ability of solving displacement in domain by solving differential equations which causes more accurate answers in domain.  We also perform well-established numerical tests and show the performance of the new element. Results shown us the accuracy and reliable answers for the introduced element. Also some benchmark examples are solved by this method and answers are compared with correct answers and plotted. High accuracy of answers with low cost of calculations and ability of the method to analysis the curve and sharp boundaries are the most important advantageous of this new element.